please; can help me in this problem ( hint: using this theorem 0òp/2cos^(2x-1)(q) sin^(2y-1)(q)dq = G(x)G(y)/2G(x+y) ) brove that: 0òp/2sin^n(q)dq = 0òp/2cos^n(q)dq = ((Öp)/2)({G(1+n)/2})/({G(2+n)/2}) thanks ;
Follow Math Help Forum on Facebook and Google+
Originally Posted by teago please; can help me in this problem ( hint: using this theorem 0òp/2cos^(2x-1)(q) sin^(2y-1)(q)dq = G(x)G(y)/2G(x+y) ) brove that: 0òp/2sin^n(q)dq = 0òp/2cos^n(q)dq = ((Öp)/2)({G(1+n)/2})/({G(2+n)/2}) thanks ; Your question is unreadable. Please improve the formatting (click on the relevant link in my signature for how to do this).
View Tag Cloud